Arsenic in porewaters of the unsaturated zone of an Argentinean watershed: Adsorption and competition with carbonate as important processes that regulate its concentration - Puccia, Virginia (2015)
The arsenic (As) concentration in porewaters of the unsaturated (vadose) zone of a watershed located in the Chaco-Pampean Plain of Argentina was investigated. A water displacement method using carbon tetrachloride was applied to the sediments in order to obtain the water samples, which could not be obtained by a simple high-speed centrifugation method. The CD-MUSIC surface complexation model was applied to calculate arsenate adsorption on sediments, arsenate concentration in porewaters in contact with the sediments and effects of carbonate. Ferrihydrite was considered to represent the active adsorbing material in the sediments. Therefore, proton adsorption (surface charge) data and arsenate adsorption isotherms obtained with a synthetic ferrihydrite were used to calibrate the CD-MUSIC model. Arsenate and carbonate concentrations in the studied porewaters were positively correlated. The model was able to predict As concentration within a factor of two in most samples. Carbonate affects As concentration by competing with arsenate species for adsorption sites on the mineral surface. As it occurs with groundwater samples of the saturated zone in many aquifers, this article shows for the first time that adsorption-desorption processes also seem to control As concentration in oxic porewaters of the unsaturated zone.